An Update on Power Quality - Dah-Chuan Lu, Dylan (IntechOpen, 2013)
Power quality is an important measure of fitness of electricity networks. With increasing renewable energy generations and usage of power electronics converters, it is important to investigate how these developments will have an impact to existing and future electricity networks. This book hence provides readers with an update of power quality issues in all sections of the network, namely, generation, transmission, distribution and end user, and discusses some practical solutions.